Analysis of Series of Measurements from Job-Centric Monitoring by Statistical Functions - Hilbrich, Marcus; Frank, Markus (Computer Science, 2017)
The rising number of executed programs (jobs) enabled by the growing amount of available resources from Clouds, Grids, and HPC (for example) has resulted in an enormous number of jobs. Nowadays, most of the executed jobs are mainly unobserved, so unusual behavior, non-optimal resource usage, and silent faults are not systematically searched and analyzed. Job-centric monitoring enables permanent job observation and, thus, enables the analysis of monitoring data. In this paper, we show how statistic functions can be used to analyze job-centric monitoring data and how the methods compare to more-complex analysis methods. Additionally, we present the usefulness of job-centric monitoring based on practical experiences.